A note on fractional powers of first-order differential and difference operators in relation to fractional derivatives - Ramil Salimov (E-Journal of Analysis and Applied Mathematics, 2025)
This paper concentrates on fractional derivatives and fractional powers of first-order differential and difference operators. It is illustrated how fractional derivatives are related to fractional powers of a first-order positive operator with boundary condition. Moreover, difference formulas for fractional derivatives are derived.